Moral panics on lgbt issues: evidence from indonesian tv programme - Listiorini, Dina; Asteria, Donna; Sarwono, Billy (Jurnal Studi Komunikasi, 2019)
There was a discussion activity conducted by a small club of the University of Indonesia called SGRC (Support Group and Resource Center on Sexuality Studies) at the beginning of January 2016. It did not only discuss sexuality such as sexual preferences but also conduct peer support for LGBT groups. However, it was reported illegal for many reasons. Although later the â€œillegalâ€ stamp was dubbed as an "internal problem" of Universitas Indonesia, the effect was unbelievable. The activity of SGRC was reported by media as â€œLGBTâ€™s attack on campusâ€, â€œLGBT is dangerous for campusâ€, et cetera. Moral, Eastern hemisphere norms, and religious excuses were the main excuses by media to judge and â€œpunishâ€ the LGBT groups. After the SGRC incident, particularly in 2016, the media, both mainstream and online, massively promoted homophobia through hate speech. The media reported the LGBT phenomenon as not only dangerous but also as entities that must be destroyed. Although not as splashy as online news, some television stations reported the case in their ways. TvOne, compared to other Indonesian TV stations, was the most often to discuss LGBT issues from 2016-2018 through a debate programme titled Indonesia Lawyers Club (ILC). The most controversial episode was the one aired on February 16 whose topic was â€œLGBT Issues is Rising, How Should We React?â€ in which a participant, a psychiatrist, was accused of delivering false information. His statement was even responded by a U.S.-based international psychiatrist association which later sent him a warning letter. This paper will explore media framing on tvOneâ€™s debate programme using Robert Entmanâ€™s Framing Methods. The result shows that through inviting certain debate participants who voiced certain statements, the TV programme promoted not only anti-LGBT actions but also homophobia.